Pengaruh Buergers Allen Exercise Terhadap Sirkulasi Dan Intensitas Nyeri Angkle Brachial - Luce Yulpina Silaban; Septiana Maryani Enjelita Simangunsong; Hendrik Berkat Nurmansari Zebua; Elis Anggeria; Patimah Sari Siregar (Universitas Haji Sumatera Utara, 2023)
Diabetes mellitus is a chronic disease in which blood sugar levels are high because the body is unable to produce or utilize insulin, so blood sugar cannot be metabolized. This causes blood circulation disorders and pain in patients with diabetes mellitus. The way to treat blood circulation disorders and pain with Buerger Allen Exercise. The purpose of this research is to understand the impact of the Buerger Allen Exercise on circulation and brachial-ankle pain in patients with diabetes mellitus. This research uses a quasi-experimental type of research with a one-group pretest-posttest design. The population in this research was 31 patients with diabetes mellitus. The method of collecting samples using saturated sampling techniques and samples obtained were 31 patients. The data collection method utilizes an observation sheet. The analysis utilized in this research utilizes univariate and bivariate analysis. The bivariate analysis utilized Wilcoxon testing. This research provides results, namely before the Buerger Allen Exercise intervention, the majority of venous ulcer disorders were 80.6%, and before the intervention, the majority of severe pain was 67.7%. After the Buerger Allen Exercise intervention, venous ulcer disorders (0.8-0.9 mmHg) decreased to 51.6%, and after the intervention, the majority of mild pain was 48.4%. Based on statistical tests there is a difference before and after the intervention showing a sig score (2-tailed) of 0.001. In conclusion, there is an effect of Buerger Allen Exercise on circulation and brachial armpit pain intensity in patients with diabetes mellitus.